2002
DOI: 10.1152/ajpheart.00966.2001
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional changes in left ventricle during normotensive and preeclamptic pregnancy

Abstract: .-Increased cardiac output in pregnancy is associated with cardiac remodeling and possible reduction in contractility, which may worsen in preeclampsia. Left ventricular (LV) geometry and function were compared between nonpregnant controls (n ϭ 12) and normotensive (n ϭ 44) and preeclamptic (n ϭ 15) pregnant women using echocardiography. Loadindependent comparisons of LV systolic function compared end-systolic stress (ESS) and rate-corrected velocity of circumferential fiber shortening (V CFC). Mean arterial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
183
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(236 citation statements)
references
References 28 publications
(33 reference statements)
26
183
2
9
Order By: Relevance
“…Reversal of chamber and hypertrophic changes of normal pregnancy has been shown to occur from a variable period of eight weeks to more than one year post delivery, due to the reversal of the haemodynamic changes associated with pregnancy 14-18. However, the proportion of subjects who reported back was too small to draw a meaningful conclusion on this and further studies are therefore suggested.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reversal of chamber and hypertrophic changes of normal pregnancy has been shown to occur from a variable period of eight weeks to more than one year post delivery, due to the reversal of the haemodynamic changes associated with pregnancy 14-18. However, the proportion of subjects who reported back was too small to draw a meaningful conclusion on this and further studies are therefore suggested.…”
Section: Discussionmentioning
confidence: 98%
“…This was in support of previous studies, which had demonstrated that the heart is enlarged by both chamber dilatation and hypertrophy as a result of the haemodynamic changes that occur in pregnancy 5. Acute physiological LVH can occur rapidly during a normal human pregnancy, as an adaptive response to increased preload and cardiac work 14. This can be demonstrated during the second trimester and is most marked at the end of pregnancy 15.…”
Section: Discussionmentioning
confidence: 99%
“…Simmons et al 36 reported that women with preeclampsia tend to decrease their TVR, whereas normotensive women show an increase from antenatal to postpartum. Our report is consistent with those previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to placental hormone production, with the degree of fall in TPVR directly associated with an increase in cardiac output (CO). 1 Progressive physiological left ventricular hypertrophy also occurs 2 With increasing parity, some of these changes become amplified. Turan et al 3 in a cross-sectional study of maternal cardiac function during pregnancy demonstrated an increased CO in parous as compared with nulliparous women and the difference increased with increasing parity.…”
Section: Introductionmentioning
confidence: 99%